Body mass index, prudent diet score and social class across three generations: evidence from the Hertfordshire Intergenerational Study. Issue 1 (6th January 2021) - Carter, Sarah; Parsons, Camille; Ward, Kate; Clynes, Michael; Dennison, Elaine M; Cooper, Cyrus
Abstract : Background: Studies describing body mass index (BMI) and prudent diet score have reported that they are associated between parents and children. The Hertfordshire Intergenerational Study, which contains BMI, diet and social class information across three generations, provides an opportunity to consider the influence of grandparental and parental BMI and prudent diet score across multiple generations, and the influence of grandparental and parental social class on child BMI. Methods: Linear regressions examining the tracking of adult BMI and prudent diet score across three generations (grandparent (F0), parent (F1) and child (F2)) were run from parent to child and from grandparent to grandchild. Linear mixed models investigated the influence of F0 and F1 BMI or prudent diet score on F2 BMI and prudent diet score. Linear regressions were run to determine whether social class and prudent diet score of parents and grandparents influenced the BMI of children and grandchildren. Results: BMI was significantly associated across each generational pair and from F0 to F1 in multilevel models. Prudent diet score was significantly positively associated between grandparents and grandchildren. Lower grandparental and parental social class had a significantly positive association with F2 BMI (F0 low social class: b=1.188 kg/m 2, 95% CI 0.060 to 2.315, p=0.039; F1 middle social class: b=2.477 kg/m 2, 95% CI 0.726 to 4.227, p=0.006). Conclusion: Adult BMI tracks across generations of the Hertfordshire Intergenerational Study, and child BMI is associated with parental and grandparental social class. The results presented here add to literature supporting behavioural and social factors in the transmission of BMI across generations.